The well sorted fine sand community from the western Mediterranean Sea: A resistant and resilient marine habitat under diverse human pressures. (May 2017) - Dauvin, Jean-Claude; Bakalem, Ali; Baffreau, Alexandrine; Delecrin, Claire; Bellan, Gérard; Lardicci, Claudio; Balestri, Elena; Sardá, Rafael; Grimes, Samir
Abstract: The Biocoenosis of Well Sorted Fine Sands (WSFS) (SFBC, Sables Fins Bien Calibrés in French) is a Mediterranean community very well delimited by bathymetry (2–25 m) and sedimentology (>90% of fine sand) occurring in zones with relatively strong hydrodynamics. In this study focused on sites located along the Algerian, French, Italian and Spanish coasts of the Western Basin of the Mediterranean Sea (WBMS) we aim to compare the structure, ecological status and diversity of the macrofauna of the WSFS and examine the effects of recent human pressures on the state of this shallow macrobenthic community. We assess the ecological status and functioning of these WSFS using three categories of benthic indices: a) five indices based on classification of species into ecological groups, AMBI, BO2A, BPOFA, IQ and IP, b) the ITI index based on classification of species in trophic groups, and c) the Shannon H' index, and the Biological Traits Analysis (BTA), which is an alternative method to relative taxon composition analysis and integrative indices. Cluster analyses show that each zone show a particular taxonomic richness and dominant species. The seven benthic indices reveal that the macrobenthos of the WSFS of the four coastal zones show good or high Quality Status, except for one location on the Algerian coast (the Djendjen site) in 1997. BTA highlights the presence of three groups of species: 1) typical characteristic species; 2) indicator species of enrichment of fine particles and organic matter, and 3) coarse sand species which are accessorily found on fine sand. Finally, the WSFS which are naturally subject to regular natural physical perturbations show a high resilience after human pressures but are very sensitive to changes in the input of organic matter. Graphical abstract: Highlights: Structure, ecological status and diversity of the macrofauna were analysed using three categories of benthic indices. Biological Traits Analysis (BTA) highlighted the presence of three groups of species. Cluster analyses showed a particular taxonomic richness and dominant species for each site. Good or high Quality Status, except for one location on the Algerian coast were found. WSFS showed a high resilience in spite of numerous human pressures.